Impact of substrate geometry on electrospun fiber deposition and alignment - Wang, Baolin; Zhou, Wenyan; Chang, Ming‐Wei; Ahmad, Zeeshan; Li, Jing‐Song (Journal of applied polymer science, 2017)
ABSTRACT Aligned, uniform fiber matrixes are highly desirable in numerous engineering and physical science applications. Here, modified electrospinning (ES) deposition substrates (paired and in parallel) are explored to achieve rapid preparation of multiple topographies. Three ES substrates with well‐defined geometries (rectangular, concave, and E‐shaped) were investigated (arranged in parallel) for their impact on fiber size, morphology, orientation, and cell behavior. The results indicate fiber alignment and orientation can be improved and modulated based on the substrate geometry. In addition, altering the interdistance space between various parallel substrates has a clear impact on fiber diameter size and alignment (random, aligned, and perpendicular orientation). Electric field simulations based on substrate geometries show greater probable regions of aligned electric field vectors and distribution, which indicates the most likely deposition attributes of electrospun PCL fibers. Fibrous PCL membranes were biocompatible, and cell growth and guidance were along the fiber path, with evidence of branching at intersecting fibers for multiaxial fibrous topographies. These findings show that the substrate geometry can be optimized to effectively assemble multiaxial layered and well‐aligned fibers in a controlled fashion, which is ideal to support several application developments dependent on fiber topography, integrity, and morphology. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44823.